Therapeutic effect of Atractylenolide I on Aspergillus fumigatus keratitis by affecting MyD88/ NF-κB pathway and IL-1β, IL-10 expression. (February 2023) - Chen, Xiaomeng; Lu, Danli; Liu, Wenting; Xie, Jianye; Lu, Zhenjun; Yang, Hua; Yan, Haijing; Wang, Limei; Che, Chengye
Abstract: Purpose: Atractylenolide I (AT-I) is a natural sesquiterpene with anti-inflammatory effects. The purpose of this study was to research the anti-inflammatory effect of AT-I on Aspergillus fumigatus(A. fumigatus) keratitis in mice. Methods: Cytotoxicity test and cell scratch test were used to determine the therapeutic concentrations of corneal infections. In vivo and in vitro studies, mouse cornea and human corneal epithelial cells (HCECs) infected with A. fumigatus were treated with AT-I or dimethyl sulfoxide (DMSO). Then, to analyze the effect of AT-I on inflammatory response, namely neutrophil or macrophage recruitment and the expression of cytokines involving MyD88, NF-κB, interleukin 1β (IL-1β) and interleukin 10 (IL-10). To study the effects of the drug, the techniques used include slit-lamp photography, immunofluorescence, myeloperoxidase (MPO) detection, quantitative real-time polymerase chain reaction (QRT-PCR), and western blot. At the same time, in order to explore the combined effect of the drug and natamycin, slit-lamp photographs and clinical scores were used to visually display the disease process. Results: No cytotoxicity was observed under the action of AT-I at a concentration of 800 μM. In mouse models, AT-I significantly suppressed inflammatory responses, reduced neutrophil and macrophage recruitment, and decreased myeloperoxidase levels early in infection. Studies have shown that AT-I may reduce the levels of IL-1β and IL-10 by inhibiting the MyD88/ NF-κB pathway. The drug combined with natamycin can increase corneal transparency in infected mice. Conclusion: AT-I may inhibit MyD88 / NF-κB pathway and the secretion of inflammatory factors IL-1 β and IL-10 to achieve the therapeutic effect of fungal keratitis.